Global trends and hotspots in Asian Art research from 1997 to 2023: a bibliometric analysis and visualization study - Mao Xing; Sarena Abdullah (Cogent Arts & Humanities)
In recent years, the field of Asian art has undergone extensive study. However, there is a fundamental gap in the bibliometric analysis of trends and directions in the field. The purpose of this article study is to provide a comprehensive review through bibliometric analysis. This study conducted a literature search in Web of Science databases, and screening included SCIE, SSCI, and A&HCI. In total, 676 studies between 1997 and 2023 were compiled and visualized using VOSviewer, SCImago software, and Bibliometrix (R package). The collected data identifies research hotspots, evolutionary processes, and the field’s development dynamics, as well as identify key themes and research directions. Studies on Asian art exhibited steady growth before 2016 but experienced a substantial increase from 2017 to 2023. This article maps publication trends, subject categories, and institutional contributions, offering insights into the geographical and institutional distribution of research. Additionally, the study analyses the author co-citation network, revealing collaborative structures within the field. The research hotspots and trends were identified through keyword clustering and timeline analysis. These findings not only provide rich references for the global perception of Asian art but also provide insights for future research.